PENGARUH LAYANAN AKADEMIK DAN LAYANAN ADMINISTRASI TERHADAP KEPUASAN MAHASISWA KEBIDANAN HAFSHAWATY ZAINUL HASAN GENGGONG PROBOLINGGO JAWA TIMUR - Maharani, Lia Kholida Putri (Jurnal Manajemen Pendidikan Islam Darussalam, 2024)
This research determines the influence of academic service and administrative services on the satisfaction of midwifery students Hafhawaty Zainul Hasan Genggong Probolinggo, East Java. This research is quantitative with a causal study design. Based on non-probability sampling with a saturated sampling approach, a sample of 150 students was obtained. The data analysis method used in this research is multiple linear regression analysis with Microsoft Excel 2019 and SPSS 26.0 software as the analysis tool. Based on the results of the research and discussion, researchers can conclude that academic service and administrative services both partially and simultaneously have a positive and significant effect on student satisfaction. Thus, the better the academic services and administrative services provided to students, the greater the satisfaction of Hafhawaty Zainul Hasan Genggong Probolinggo, East Java midwifery students (p-value <0.05). This research was only carried out by the Hafshawaty Zainul Hasan Genggong Midwifery Academy, Probolinggo, East Java, and does not use control variables as other variables that could influence student satisfaction. This research highlights that educational institutions should prioritize improving academic and administrative support systems to ensure students have a satisfying experience during their studies.